2023
DOI: 10.1001/jamanetworkopen.2023.36728
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Aspects of Physician Decision-Making for Deprescribing Among Older Adults With Dementia

Jonathan D. Norton,
Chan Zeng,
Elizabeth A. Bayliss
et al.

Abstract: ImportancePhysicians endorse deprescribing of risky or unnecessary medications for older adults (aged ≥65 years) with dementia, but there is a lack of information on what influences decisions to deprescribe in this population.ObjectiveTo understand how physicians make decisions to deprescribe for older adults with moderate dementia and ethical and pragmatic concerns influencing those decisions.Design, Setting, and ParticipantsA cross-sectional national mailed survey study of a random sample of 3000 primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Most physicians reported that withdrawing medications prescribed by another clinician is an ethical challenge. This was also considered as a potential ethical barrier to deprescribing by Norton et al ( 2023 ) in 3000 primary care physicians who care for older adults with dementia. Physicians are more eager to deprescribe antibiotics initiated by themselves than when the therapy was initiated by others (Llor, Cordoba, et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most physicians reported that withdrawing medications prescribed by another clinician is an ethical challenge. This was also considered as a potential ethical barrier to deprescribing by Norton et al ( 2023 ) in 3000 primary care physicians who care for older adults with dementia. Physicians are more eager to deprescribe antibiotics initiated by themselves than when the therapy was initiated by others (Llor, Cordoba, et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%